Uji Tiga Jenis Media Tumbuh Trichoderma sp. dan Efektifitas Antagonisme Terhadap Fusarium sp. Secara Invitro - Erna Prastyawati Nengsih; Mazidatul Faizah; Hari Prasetyono (AGROSAINTIFIKA, 2022)
Test of three types of growth media Trichoderma sp. and the effectiveness of antagonists against Fusarium sp. in vitro. Trichoderma sp. is a fungus that is found in almost all types of soil and is one type of fungus that can be used as a biological agent to control plant pathogens. Fungal growth is generally strongly influenced by a number of factors including temperature, light, air, pH and nutrients such as carbon and nitrogen such as PDA, bran and banana peels. This study aims to obtain effective conidia that meet the requirements as biological agents, and the media is easy to obtain and the price is relatively cheap. The results showed that the most effective medium was PDA media, namely the number of spores (6.7 x 108), viability (90.66%) and inhibition reached (68.11%), but relatively expensive. While the bran media showed results below PDA media, namely the number of spores (4.8 x 108), viability / germination (89.33%), and the antagonism test of Trichoderma sp. against Fusarium sp. The results of propagation on bran media had an inhibitory power of up to (62.22%) so that the media could be used as an alternative as a substitute medium. Furthermore, the number of banana peel media spores (2.58 x 108), viability (85.33%) and inhibition (61.48%). Key Word : Effectiveness, Medium , Trichoderma sp, Fusarium sp, Antagonism. PENDAHULUAN